2017
DOI: 10.1155/2017/4269875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Channel Blockers on Lower Urinary Tract Symptoms: A Systematic Review

Abstract: Background Numerous medications are known to be associated with the development of lower urinary tract symptoms (LUTS). One such medication group is calcium channel blockers (CCB). Objective To critically examine the literature regarding the involvement of CCB in manifestation of LUTS in humans. Methods A systematic literature search was conducted on PubMed, SciELO, Scopus, and OpenGrey databases to find all potentially relevant research studies before August 2016. Results Five studies met the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A review article 6 identified five studies [7][8][9][10][11] investigating the relationship between CCB and storage LUTS. However, the results of this review were inconclusive: three studies demonstrated a link between CCB and LUTS/ nocturia; one study found no significant link; and one study reported an inverse relationship between CCB use and nocturia.…”
mentioning
confidence: 99%
“…A review article 6 identified five studies [7][8][9][10][11] investigating the relationship between CCB and storage LUTS. However, the results of this review were inconclusive: three studies demonstrated a link between CCB and LUTS/ nocturia; one study found no significant link; and one study reported an inverse relationship between CCB use and nocturia.…”
mentioning
confidence: 99%
“…Previous reports found that dyslipidemia is proportional to visceral fat volume and that some antihypertensive drugs could affect LUTS. 9,18,19 Furthermore, patients with malignancies could face a risk of developing sarcopenia. 2 Thus, we also disclosed the prior history of malignancies and the use of antihypertensive and antihyperlipidemic drugs in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, associations of hypertension and AHTs with nocturia were demonstrated [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Especially, CCB use was reported to be positively associated with nocturia [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, associations of hypertension and AHTs with nocturia were demonstrated [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Especially, CCB use was reported to be positively associated with nocturia [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Bulpit et al and Hollenberg et al demonstrated that the CCBs amlodipine and/or nifedipine promote nocturia and increased urination compared to the aldosterone antagonist eplerenone or β-blocker bisoprolol [ 23 , 24 ], while Hall demonstrated that CCB use as monotherapy or combination with other AHTs, but not AHTs other than CCBs, was significantly associated with increased prevalence of nocturia (OR 2.65) in women aged less than 55 but not in those aged 55 or more [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation